Epidemiological profile of deaths from leukemia in Brazil from 2018 to 2023 (Research, Society and Development, 2024)
Leukemias are neoplasms that affect hematopoietic tissue. These neoplasms do not have a completely known etiology, however, it is known that they are related to a complex set of factors, which include various mutations, infections, environmental exposure and lifestyle habits. Leukemias are classified according to the cell lineage affected and how the disease progresses. This diverse group of neoplasms is related to several deaths annually throughout the world. The objective of this study was to epidemiologically characterize leukemia deaths recorded in Brazil during the period from January 2018 to October 2023. For this study, mortality data were collected from the Department of Informatics of the Unified Health System (DATASUS). The data were tabulated and descriptive statistics were performed. The five regions of the country were considered (north, south, central-west, southeast and northeast), male and female sexes, age groups from 0 to over 80 years old and races/color (white, brown, black, without information, yellow and indigenous). From data analysis, it was observed that the highest number of deaths was concentrated in the southeast region. Other factors such as male sex and older age group were associated with higher mortality from leukemia. Regarding the assessment of races, more deaths were observed among white individuals. It is possible that the socioeconomic differences present between different regions of the country and races have an impact on access to health services, adequate diagnosis and notification.